A Population-Based Survey on Perceptions of Opioid Treatment and Palliative Care Units: OPTIM Study. (March 2014) - Igarashi, Ayumi; Miyashita, Mitsunori; Morita, Tatsuya; Akizuki, Nobuya; Akiyama, Miki; Shirahige, Yutaka; Eguchi, Kenji
This study aimed to clarify the general public's perceptions of opioids and palliative care units (PCUs) and explore factors related to such perceptions. A cross-sectional, anonymous questionnaire was administered to 8000 people. Although a majority agreed with positive perceptions of opioids and PCUs, some also agreed with negative perceptions, such as opioids are addictive and shorten life (28% and 27%, respectively). Multiregression analyses revealed that respondents with a better knowledge of PCUs had higher positive perceptions than those without such knowledge ( P <.001). The higher positive perceptions were associated with a higher sense of security regarding regional cancer care ( P < .001). Providing the general public with adequate knowledge about palliative care may improve perceptions of palliative care and the sense of security.